EFFECTIVENESS OF THE APPLICATION OF INNOVATION AND DIGITAL FINANCIAL TECHNOLOGIES IN EXPORT FINANCING - Turayeva Yulduz Shamsiddinovna (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
In the context of the rapid digitalization of the world economy, the complexity of international trade chains and the integration of financial markets, the issue of effective financing of export activities is becoming more urgent than ever. World practice shows that, although traditional financial mechanisms in export processes - bank loans, letters of credit, export insurance and state guarantees - do not lose their importance, their effectiveness is increasingly manifested in combination with digital technologies and innovative financial solutions.